2019
DOI: 10.1088/2515-7620/ab0dab
|View full text |Cite
|
Sign up to set email alerts
|

Strengthening of the Walker Circulation in recent decades and the role of natural sea surface temperature variability

Abstract: In response to global warming, climate model simulations suggest a weakening of the Walker Circulation (WC), which is supported by long-term sea level pressure observations over the 20th century. Here, we show the observations and multiple reanalyses yield the opposite trend from 1979 to present−a WC intensification. Atmosphere-only simulations driven by the real-world evolution of sea surface temperatures (SSTs) simulate this observed intensification, whereas coupled ocean atmosphere simulations do not. Thus,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
14
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 42 publications
2
14
0
Order By: Relevance
“…The positive deviations from the expected central Pacific OLR and the associated EQSOI during these recent events relate to a significant multidecadal trend of increasing central Pacific OLR and a strengthening Walker circulation, which is consistent with several recent studies (Hu et al, 2013;L'Heureux, Lee, et al, 2013;Sandeep et al, 2014;Seager et al, 2019;Sohn & Park, 2010;Solomon & Newman, 2012;Zhao & Allen, 2019) but inconsistent with the expected response to rising global temperatures from global climate models and through basic thermodynamic arguments Sohn et al, 2013;Vecchi et al, 2006). Given that this study is limited to a 40-year observational record, the reasons for this discrepancy are beyond the scope of this study (see, for example, Liu & Xie, 2018;Seager et al, 2019;Xie & Kosaka, 2017).…”
Section: Discussionsupporting
confidence: 91%
“…The positive deviations from the expected central Pacific OLR and the associated EQSOI during these recent events relate to a significant multidecadal trend of increasing central Pacific OLR and a strengthening Walker circulation, which is consistent with several recent studies (Hu et al, 2013;L'Heureux, Lee, et al, 2013;Sandeep et al, 2014;Seager et al, 2019;Sohn & Park, 2010;Solomon & Newman, 2012;Zhao & Allen, 2019) but inconsistent with the expected response to rising global temperatures from global climate models and through basic thermodynamic arguments Sohn et al, 2013;Vecchi et al, 2006). Given that this study is limited to a 40-year observational record, the reasons for this discrepancy are beyond the scope of this study (see, for example, Liu & Xie, 2018;Seager et al, 2019;Xie & Kosaka, 2017).…”
Section: Discussionsupporting
confidence: 91%
“…We finally examine trends in the ELI (Figure 5f), as prior studies have shown that ENSO is a significant driver of global TC activity (e.g., Camargo et al, 2007). The 1990-2021 period exhibited a statistically significant westward shift in the annually averaged ELI, indicating a stronger and westward-shifted Walker Circulation, as recently noted by Seager et al (2019) and Zhao and Allen (2019). This trend toward a more La Niña-like base state is consistent with observed atmospheric/oceanic pattern changes as well as the observed decreasing trend in western North Pacific ACE and increasing trend in North Atlantic ACE since 1990.…”
Section: Large-scale Drivers Of Observed Trendsmentioning
confidence: 85%
“…An in‐depth analysis of these causes is beyond the scope of this paper, but we discuss some possible explanations found in the current literature. One of the reasons for the diminished DIC ′ variability may be related to the fact that models simulate a weaker Walker circulation in response to global warming (Vecchi et al., 2006; Zhao & Allen, 2019). A weaker Walker circulation would weaken the upwelling of DIC‐rich waters during La Niña conditions.…”
Section: Resultsmentioning
confidence: 99%